OPTIMALISASI KINERJA KOLOM FRAKSINASI DI PT X - Suharto Suharto (Industrika : Jurnal Ilmiah Teknik Industri, 2019)
Fractionation column in PT X is a unit of equipment that aims to separate the gas component wherein the composition is primarily a mixture of propylene and propane C3 to C4 mixture. Based on the calculation of the operating data obtained results C3 on product purity level of 98.92% upper and purity levels of C4 in the bottom product of 86.27%. From the correlation analysis of process variables on the dependent variable that is used as a parameter optimization are purity levels of C3 in the top products and product purity C4 at the bottom of the results showed that the most significant process variables influence is a bottom temperature and the amount of reflux flow. Of the two variables are then conducted regression analysis to optimize the parameters to obtain the objective function. Based on the results of the objective function obtained optimal condition is a bottom temperature of 108,04oC and reflux amount of 61.44 tons/hour. Then the results obtained purity levels of C3 in the upper part of the product is 99.99% and purity of C4 at the bottom of the product by 97.00%. Of the economic calculation under optimal conditions fractionation column will be obtained potential profit of Rp 44,346,666 /day. Keywords: Optimization, Performance, Fractionation